Integrated nutrient management to improve soil health, nutrient uptake and growth of Poplar (Populus deltoides) seedlings in nursery conditions - Khipla, Neha; Kaur, Jupinder; Gosal, S.K.; Gill, R.I.S.; Walia, S.S. (Indian Journal of Agroforestry, 2021)
Agricultural sustainability can never be achieved until dependence on chemicals for soil fertilization is reduced. Integrated nutrient management is a step towards sustainable management of soil, where optimum nutrition is provided to plants through integration of nutrient sources. This study was aimed to evaluate the combinations of inorganic fertilizers (75 and 100% of recommended N and P fertilizers) and biofertilizers (PSB, Azotobacter and consortium) to influence soil chemical properties, nutrient uptake and growth of poplar (clone PL-5) in nursery conditions. All the observed parameters (except soil pH) were found significantly (p<0.05) higher in inoculated treatments than uninoculated controls. Among inoculated treatments, highest soil organic carbon, available N, P and K content was recorded under consortium biofertilizer + N100P100. Along with complete fertilizer dose, the highest plant N and K uptake was recorded under Azotobacter inoculation; whereas, plant P uptake under consortium inoculation. Plant growth attributes viz., leaf number per plant, shoot length and biomass were found highest with application of Azotobacter biofertilizer + N100P100. The effect of consortium and Azotobacter inoculation was equivalent in improving stem collar diameter, root length and biomass; but it was higher than that with PSB inoculation. It is concluded that integrating biofertilizers with inorganic fertilizers can improve their fertilizer use efficiency and benefit soil health on a long term basis. Further, microbes used as consortium can function by means unique from monocultures, and thus, we suggest N100P100 + consortium as an ideal fertilizer strategy for efficient nutrition and growth of poplar.